MINIMAL INVASIVE PARATHYROIDECTOMY IN A PATIENT OF PARATHYROID ADENOMA - A CASE STUDY - Syed Hashim Ali Inam (Army Medical College Rawalpindi, 2020)
Frequently, the kidney stones are treated without determining the root cause of kidney stones which leads to recurrence of the kidney stones. This is a case report of a forty nine years old male who developed nephrolithiasis secondary to parathyroid adenoma. This tumor was removed through a modern and an efficient technique called minimal invasive parathyroidectomy which proved to be more efficient and safe compared to the old techniques.